ASUHAN KEBIDANAN KEHAMILAN DI PRAKTIK MANDIRI BIDAN (PMB) SYAFRIANI KECAMATAN NIBONG KABUPATEN ACEH UTARA - Maulidyarni; Putri, Hendrika Wijaya Kartini (JURNAL KESEHATAN ALMUSLIM, 2022)
Based on the results of the 2015 Inter-Census Population Survey (SUPAS), the Maternal Mortality Rate (MMR) in Indonesia is still high at 305/100,000 live births. Destination; provide obstetric care for Mrs. R in the Independent Practice of Midwife Syafriani, Nibong District, North Aceh Regency according to midwifery service standards using Varney’s midwifery management and documented by the SOAP method. This type of report is in the form of a case study, carried out at PMB Syafriani, Nibong District, North Aceh Regency from December 21, 2021 to January 10, 2022, the subject is Mrs. R 35 years old with GIII, PII, A0, HPHT: 06-07-2021, TTP: 13-04-2022. Pregnancy care that has been carried out on Mrs. R for 3 visits, namely the first visit on 21 December 2021, the second visit on 28 December 2021 and the third visit on 10 January 2022, the care provided is in accordance with the 14 T standard, namely: Weigh and measure height body weight, blood pressure, uterine fundal height, tetanus toxoid, fe tablets, PMS test, interview, hemoglobin examination, breast care, pregnancy exercise, urine protein examination for indications, urine glucose examination for indications, administration of iodine capsule therapy, administration of anti-inflammatory drugs malaria in endemic areas. However, there are treatments that are not carried out, namely: TT immunization, PMS examination, urine protein examination, urine glucose examination and iodine capsule therapy, this is also not done because the mother is not identified with certain diseases. It is hoped that patients will always have an awareness that the importance of health during pregnancy is to prevent maternal and infant mortality.